TAVR Suitable Procedure for High-Risk AS Patients: 5-Year Results from the PARTNER Trial - Vinall, Maria (MD Conference Express, 2014)
One-, 2-, and 3-year data from the Placement of Aortic Transcatheter Valves study [PARTNER; NCT00530894] showed significant reductions in all-cause mortality, cardiac mortality, and rehospitalization [Kapadia SR et al. Circulation. 2014; Makkar RR et al. N Engl J Med. 2012; Leon MB et al. N Engl J Med. 2010]. This article reports the 5-year outcomes for the PARTNER trial.